Measured and modeled interactive effects of potassium deficiency and water deficit on gross primary productivity and light-use efficiency in Eucalyptus grandis plantations - Christina, Mathias; Le Maire, Guerric; Battie-Laclau, Patricia; Nouvellon, Yann; Bouillet, Jean-Pierre; Jourdan, Christophe; Moraes Goncalves, Jose Leonardo de; Laclau, Jean-Paul [UNESP] (Wiley-Blackwell, 2015)
Global climate change is expected to increase the length of drought periods in many tropical regions. Although large amounts of potassium (K) are applied in tropical crops and planted forests, little is known about the interaction between K nutrition and water deficit on the physiological mechanisms governing plant growth. A process-based model (MAESPA) parameterized in a split-plot experiment in Brazil was used to gain insight into the combined effects of K deficiency and water deficit on absorbed radiation (aPAR), gross primary productivity (GPP), and light-use efficiency for carbon assimilation and stem biomass production (LUEC and LUEs) in Eucalyptus grandis plantations. The main-plot factor was the water supply (undisturbed rainfall vs. 37% of throughfall excluded) and the subplot factor was the K supply (with or without 0.45mol Km(-2)K addition). Mean GPP was 28% lower without K addition over the first 3years after planting whether throughfall was partly excluded or not. K deficiency reduced aPAR by 20% and LUEC by 10% over the whole period of growth. With K addition, throughfall exclusion decreased GPP by 25%, resulting from a 21% decrease in LUEC at the end of the study period. The effect of the combination of K deficiency and water deficit was less severe than the sum of the effects of K deficiency and water deficit individually, leading to a reduction in stem biomass production, gross primary productivity and LUE similar to K deficiency on its own. The modeling approach showed that K nutrition and water deficit influenced absorbed radiation essentially through changes in leaf area index and tree height. The changes in gross primary productivity and light-use efficiency were, however, driven by a more complex set of tree parameters, especially those controlling water uptake by roots and leaf photosynthetic capacities.
Keywords: Carbon assimilation; Eucalypt; Fertilization; Modeling; Nutrient shortage; Radiation-use efficiency; Tree traits